University student perceptions of English skills assessment - Suek, Leni Amelia (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2020)
Investigating students perspectives on assessment has been widely studied, however, relatively little is known about how university students respond to assessment. Assessment is an important part of teaching and learning process because it is used to measure students knowledge, skills and also to evaluate the program. Students perspectives are particularly important because the power of assessment directly impacts on their motivation and attitudes towards learning. This study focused on finding out the student perceptions of the test, test result, test procedure and feedback of four skill-subjects that they had taken. The study explored the students opinions of English language assessment in English Department of Universitas Nusa Cendana, Kupang, East Nusa Tenggara, Indonesia through the draw and write technique and interview. The results showed that assessment might cause positive or negative feelings among the students. This paper helps understand how assessment impacts the students lives, how teacher can make a well-designed assessment to measure the students ability and skills properly without discouraging them from learning, and how the draw and write technique can be used to document the student perceptions.